Virtual keyboard based on a brain-computer interface - Rusanu, O A; Cristea, L; Luculescu, M C; Cotfas, P A; Cotfas, D T (IOP Publishing, 2019)
This paper proposes a novel LabVIEW based algorithm regarding the implementation of an eye-blinks strength controlled virtual keyboard aimed to help people with neuromotor disabilities. The application can be considered a brain-computer interface which is useful for the assistance of patients suffering from Locked-In syndrome or amyotrophic lateral sclerosis. A precise, repeatable and easily detectable control signal could be the eye-blink strength. The LabVIEW based virtual keyboard provides the following features: detection and counting the voluntary eye-blinks, switch command, select command, highlight action running in parallel with the previously mentioned processes, enabling cancel, delete and space commands. The working principle underlying the implementation of the proposed virtual keyboard is Divide and Conquer paradigm. Thus, it is possible the switching task across the rows, half rows and keys (characters) in order to select a row, half row, respectively key associated to the character that should be introduced in the text box.